Langevin equation approach to granular flow in a narrow pipe - Riethmüller, Tino; Schimansky-Geier, Lutz; Rosenkranz, Dirk; Pöschel, Thorsten (Journal of Statistical Physics, 1997)
The gravity-driven flow of granular material through a rough, narrow vertical pipe is described using the Langevin equation formalism. Above a critical particle density the homogeneous flow becomes unstable with respect to short-wave length perturbations. In correspondence with experimental observations, we find clogging and density waves in the flowing material.
Keywords: Flow of solids; Granular material; Stochastic processes